Determinants of Mudharabah Term Deposit: A Case of Indonesia Islamic Banks - Umam, Fachru Nurul; Salam, Annisa Nur; Rizal, Achmad (Journal of Economics Research and Social Sciences, 2021)
The growth of Islamic finance industries in Indonesia has shown significant improvement. The increased number of surplus units depositing their funds in Islamic banks has become a significant factor in their trust and confidence in Islamic banking products. One of the products utilized by the depositor is the mudharabah deposit product, where the Islamic bank offers higher profit compared to other types of deposit or saving. This paper aims to analyze the issues in a mudharabah term deposit in the Islamic banking industry in Indonesian Islamic banks. The issues concern more on the profit and risk in the mudharabah concept that has been applied in Islamic banks and the variables that affect the changes in mudharabah deposit product. We used the sample to analyze the issues by selecting 14 Islamic banks in Indonesia from 2011-2020.Â  This research uses a quantitative approach with multiple linear regression analysis methods. Several variables are considered the independent variables to know the changes in the demand of mudharabah deposits in the Islamic bank, including interest rate, profit rate, number of office or branch units, and non-performing financing. Our analysis shows that the number of offices or branch units and non-performing financing positively impact the changes in demand of mudharabah deposits, while the interest rate and profit rate have a negative impact on mudharabah deposits.